Inequality and social unrest in India - Mathieu Couttenier; Jérémy Laurent-Lucchetti; Lore Vandewalle (Graduate Institute of International and Development Studies, 2023)
We show that inequality triggers social unrest in rural India. We develop a theoretical framework where social unrest is rationally used by civilians to oppose (unfair) surplus sharing by the elite. We predict that the probability of observing social unrest in a village increases with the sum of distances between the (log) average and the lowest incomes. We bring our measure to the data using bank account details in 2,197 Indian villages. We document that a 10% increase in our inequality measure increases by 6.5% the unconditional probability of observing social unrest in a village in a given month.
Keywords: D31; D63; D74; 330; Inequality; Social unrest; Development; Redistribution